Psychometric evaluation and invariance of the Spanish version of the Block Fat Screener (BFS-E) in university students - Saintila, Jacksaint; Morales-García, Wilter C.; Calizaya-Milla, Yaquelin E.; Ruiz Mamani, Percy G.; Huancahuire-Vega, Salomón; Calizaya-Milla, Sergio E.; Ramos-Vera, Cristian (Frontiers in Psychology, 2023)
University students constantly face a number of health challenges related to an un-healthy diet, characterized by a high intake of saturated fats. Objective: This study aimed to analyze the psychometric properties of the Spanish version of the Block Fat Screener (BFS-E) food frequency questionnaire in a university population. An observational analytical study of instrumental type was carried out in 5608 Peruvian university students. Based on the Block Fat Screener questionnaire, a back-translation and cultural adaptation process was carried out. The validity of the questionnaire was determined through exploratory factor analysis (EFA) and con-firmatory factor analysis (CFA), hypothesizing a unidimensional structure. For the determination of reliability, the alpha coefficients were considered, ω to assess the construct and the H coefficient. with a model that explains 63% of the accumulated variance. The CFA confirmed the unidimensionality of the 16-item questionnaire with appropriate goodness-of-fit indicators; therefore, which model of the Peruvian version adequately fits the observed data. The values of the reliability coefficients were higher than 0.90, with ordinal α=0.94, ω =0.94, and H=0.95. The Spanish ver-sion of the Block Fat Screener (BFS-E) food frequency questionnaire presents ade-quate psychometric properties and is therefore a valid scale to quickly measure fat intake in university students in a Latin American context.